Providing volunteer computing at the infrastructure level to support e-science applications - Gutierrez, Felipe; Barreto, Marcos; Gomes, Antônio Tadeu Azevedo (Anais do Brazilian e-Science Workshop (BreSci), 2013)
Cloud computing has become a well-established model to deliver on deIt has mand storage and processing resources for several types of applications. the same characteristic of elastic processing power present in volunteer computing, which relies on an increasing number of resources shared for a limited period. In this paper, we present the integration of the BOINC volunteer computing middleware at the infrastructure level with a platform providing support for e-science applications at the user interface level. Two case studies on protein docking and number sorting are discussed in order to show how BOINC relates with such platform.